Effect of upfront intensive therapy on oncological outcomes in older patients with high tumor burden metastatic castration‐sensitive prostate cancer: A multicenter retrospective study. Issue 13 (23rd June 2022) - Miura, Yuki; Hatakeyama, Shingo; Narita, Shintaro; Kimura, Takahiro; Hata, Kenichi; Yanagisawa, Takafumi; Tanaka, Toshikazu; Ishi, Noritaka; Kawamura, Sadafumi; Hoshi, Senji; Ishidoya, Shigeto; Mitsuzuka, Koji; et al.
Abstract: Background: The effect of upfront intensive therapy on the prognosis of older patients with metastatic castration‐sensitive prostate cancer (mCSPC) remains unclear. Thus, we assessed the impact of older age (≥75 years) on oncological outcomes in mCSPC patients with a high tumor burden. Methods: This multicenter retrospective study included 252 patients aged ≥75 years treated with either upfront or conventional therapy between 2014 and 2021. We compared castration‐resistant prostate cancer (CRPC)‐free survival (FS) and overall survival (OS) between patients with androgen deprivation therapy (ADT) plus upfront intensive therapy (docetaxel [DTX] or abiraterone acetate [ABI] plus prednisolone) and conventional therapy (ADT monotherapy or ADT combined with bicalutamide). We evaluated the effect of upfront intensive therapy on prognosis by multivariable Cox regression analysis. Results: The 231 patients enrolled in our study were classified in the conventional group ( n  = 148) or the upfront group ( n  = 104; DTX = 27 and ABI = 77). The upfront group had significantly prolonged CRPC‐FS and OS compared with the conventional group, and this was also the case in the background‐adjusted multivariable Cox regression analysis. Conclusion: Patients aged ≥75 years who received upfront intensive therapy had significantly longer CRPC‐FS and OS compared with similar age patients treated with conventional therapy in real‐world practice. The oncological benefit may not diminish in this older population.